2021
DOI: 10.1136/rmdopen-2020-001472
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rituximab in peripheral ulcerative keratitis associated with rheumatoid arthritis

Abstract: ObjectivePeripheral ulcerative keratitis (PUK) is a rare but severe ocular complication of rheumatoid arthritis (RA). It can be considered as an ocular manifestation of rheumatoid vasculitis (RV). Our case series aimed to evaluate the efficacy of rituximab (RTX) for PUK occurring in patients with RA.MethodsStudy population were patients with RA-associated PUK treated with RTX 1000 mg on days 1 and 15 at least once after the diagnosis. We identified patients referred to the rheumatology and ophthalmology depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, we include RTX in Figure 3 based on previous reports. 9 , 26 , 33 36 Ocular manifestations in RA not only may be related to the underlying disease but also it may be due to the adverse ocular reactions secondary to treatment with nonsteroidal anti-inflammatory drugs (NSAIDs) and DMARDs, both synthetic and biological, in patients with RA. 37 …”
Section: Discussionmentioning
confidence: 99%
“…However, we include RTX in Figure 3 based on previous reports. 9 , 26 , 33 36 Ocular manifestations in RA not only may be related to the underlying disease but also it may be due to the adverse ocular reactions secondary to treatment with nonsteroidal anti-inflammatory drugs (NSAIDs) and DMARDs, both synthetic and biological, in patients with RA. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Patients who fail combination corticosteroid and cytotoxic therapy can be started on one of the biologics. 16,31,33,88,121,125,126,127 Geetha et al 128 compared rituximab with oral CyP in ANCAassociated vasculitis, and found that it was non-inferior to CyP and possibly better at preventing relapsing disease. 128 A recent study showed greater efficacy of the non-TNFα agents in the management of PUK.…”
Section: Systemicmentioning
confidence: 99%
“…Corneal perforation is a severe complication of PUK, which can be managed by several ways, including corneal glue, multi-layer amniotic membrane or a corneal patch graft (full thickness or lamellar). 11,125,126 Corneal glue is a simple office procedure to seal a small corneal perforation. 20 This is often a temporising procedure before definitive surgery; however, this occasionally may allow for healing without further surgery.…”
Section: Tectonicmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 167 , 168 ] A recent small case series also reported success in the treatment of RA-associated PUK, with excellent control of ocular inflammation, and also improvement in the articular and vasculitic disease. [ 169 ] In addition to rituximab, tocilizumab, and belimumab are non-anti TNF antibodies to IL-6R and BAFF, respectively, that have been used sparingly but successfully in the treatment of PUK. In one case series of patients treated with rituximab, tocilizumab, or belimumab, these agents were found to be more effective than anti-TNF agents for treatment-resistant PUK.…”
Section: Introductionmentioning
confidence: 99%